Dentate gyrus-specific knockdown of adult neurogenesis impairs spatial and object recognition memory in adult rats - Jessberger, Sebastian; Clark, Robert E; Broadbent, Nicola J; Clemenson, Jr, Gregory D; Consiglio, Antonella; Lie, D Chichung; Squire, Larry R; Gage, Fred H (Learning & memory (Cold Spring Harbor, N.Y.), 2009)
New granule cells are born throughout life in the dentate gyrus of the hippocampal formation. Given the fundamental role of the hippocampus in processes underlying certain forms of learning and memory, it has been speculated that newborn granule cells contribute to cognition. However, previous strategies aiming to causally link newborn neurons with hippocampal function used ablation strategies that were not exclusive to the hippocampus or that were associated with substantial side effects, such as inflammation. We here used a lentiviral approach to specifically block neurogenesis in the dentate gyrus of adult male rats by inhibiting WNT signaling, which is critically involved in the generation of newborn neurons, using a dominant-negative WNT (dnWNT). We found a level-dependent effect of adult neurogenesis on the long-term retention of spatial memory in the water maze task, as rats with substantially reduced levels of newborn neurons showed less preference for the target zone in probe trials >2 wk after acquisition compared with control rats. Furthermore, animals with strongly reduced levels of neurogenesis were impaired in a hippocampus-dependent object recognition task. Social transmission of food preference, a behavioral test that also depends on hippocampal function, was not affected by knockdown of neurogenesis. Here we identified a role for newborn neurons in distinct aspects of hippocampal function that will set the ground to further elucidate, using experimental and computational strategies, the mechanism by which newborn neurons contribute to behavior.